Mô phỏng một hệ động học phi tuyến, không dừng chịu tác động của nhiễu - Từ, Phan Văn (Journal of Computer Science and Cybernetics, 2016)
This paper is using SIMULNK for the model building of the dynamic nonlinear, time-variable system under acting of a noise, e.g. the control system of fly equipment. These results showed the noise influence on system variables, that gave us decision to use or to resist the noise influence for system control.